Reemergence of Lost Paradigm: Polluter Pays Principle - A. M. Kamal (Московский журнал международного права, 2009)
This article presents my personal narrative, in the epistemology of a new but mostly deserted subject ‘Polluter Pays Principle’. It addresses the complex issues of transnational environmental law that have a profound relationship with Polluter Pays Principle. To give some context to the discussion, first portion of this article briefly discusses the definition of Polluter Pay Principle and its history. Further, it analyses the issues of liability, standard of proof that requires for establishing a polluting event, and its limitation period. It particularly focuses on the criticisms of Polluter Pays Principle. It is hoped that the results of this research would attract the attention of policy-makers, and rigorous legal safeguards should be implemented to protect the environment from future abuse.